COMPARISON OF THE EFFECT OF GAZE STABILITY EXERCISES WITH TAI CHI EXERCISES ON THE DYNAMIC BALANCE OF THE ELDERLY AT PSTW BUDI MULIA IV, EAST JAKARTA - Achwan, Achwan; Kurniasari, Fitria; Trioclarise, R. (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
Background: The decline in the elderly's ability to function is decreasing over time, one of the problems is balance. Balance is the body's ability to maintain the center of gravity both in static and dynamic conditions. Decreased dynamic balance in the elderly can increase the risk of falls. Gaze stability exercises and tai chi exercises are types of exercise to improve the dynamic balance of the elderly. Objective: To determine the difference in the effect of gaze stability exercises and tai chi exercises on the dynamic balance of the elderly. Method: This research used a quasi-experimental research design with a pre-test and post-test two-group design. The sampling technique used a purposive sampling method which met the inclusion and exclusion criteria with a sample size of 26 people consisting of two intervention groups. The dependent variable of the research is the dynamic balance of the elderly, measured using the Timed Up and Go Test. The independent variables are gaze stability exercises and tai chi exercises which are done 3 times a week for 3 weeks. Results: The mean dynamic balance of the elderly in the gaze stability exercise group before intervention and after intervention was 25.29 and after 20.06 with a p-value of 0.000 with a mean difference of 3.09, while the mean for the tai chi exercise group before intervention was 23.06 and after 20.06 with a mean difference of 3.00. Bivariate analysis of the two groups using Paired Sample T-test resulted in a p-value of 0.000. The Independent T-Test showed a p-value of 0.411. Conclusion: The two groups given gaze stability exercises and tai chi exercises had the same significant effect. Both groups had the same effectiveness in improving the dynamic balance of the elderly.